Advanced parallel processing technologies : 12th International Symposium, APPT 2017, Santiago de Compostela, Spain, August 29, 2017, Proceedings /: 12th International Symposium, APPT 2017, Santiago de Compostela, Spain, August 29, 2017, Proceedings. (2017) - Unknown
No abstract available